Gambaran Teknik, Frekuensi Dan Waktu Menyikat Gigi Pada Anak Tunanetra Di Slb Citeureup Kota Cimahi - Harwati Nur Rahmah; Nurul Fatikhah; Sri Mulyanti; Ulfah Utami (Poltekkes Kemenkes Bandung, 2022)
Health is very important for every human being, dental health problems in Indonesia are relatively high, especially children with special needs, namely the visually impaired, have lower levels of dental and oral health and hygiene when compared to the normal group. This study aims to determine the description of the technique, frequency and time of brushing teeth in blind children at Citeureup Special School, Cimahi City. This research is descriptive qualitative by using interview and video brushing methods. The research was carried out at the Citeureup Special School, Cimahi City. The study was conducted on the blind with a sample of 16 respondents. Primary data obtained from the checklist sheet will be presented in the form of a frequency distribution table, the results are analyzed to obtain an overview or information. The results showed that the overall knowledge of brushing techniques was 100% of respondents using the horizontal technique and 0% of respondents using the roll technique. The frequency of brushing teeth in blind children was 87.5% already answered 2x a day and the time of brushing teeth in blind children was 31, 2% have answered 2 times in the morning after breakfast and at night before going to bed.